'Heavy Fog in the Channel — Continent Cut Off': Reform of Upper-Secondary Education from the Perspective of English Exceptionalism. (December 2014) - Hodgson, Ann; Spours, Ken
Recent international studies in upper-secondary education (USE) have highlighted the importance and complexities of this phase as it becomes a more universal experience. Here the authors examine recent trends in USE to provide a context for discussion of the English system, which has been moving from a 'linked' to a more 'tracked' approach since 2010 through a combination of factors that make it 'exceptionalist'. They suggest that this change has not been adequately captured in crossnational studies because of its recent nature and because analysis of USE systems has not sufficiently appreciated the multi-dimensional character of this phase of education as it expands. They argue that the wider global trends and pressures in USE are towards integration and unification rather than segregation and tracking. In this context they explore a four-dimensional integrated/unified model for the English USE system that might bring it closer to other systems in the UK and in Europe, thus reducing its exceptionalism and dispelling the 'fog in the Channel'. They conclude the article by arguing that as USE systems expand and become more universal, they require a multi-dimensional analysis, and the model discussed here may be appropriate more widely.